VISNYKIVSTVO AND VISNYKIVTSI: FIGURES AND ISSUES - Salyha , T. Yu. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In ideological and aesthetic concept of “visnykivstvo” and particularly “artistic ideology” of Dmitry Dontsov interpreted some vectors poetry E. Malaniuk and O. Lyaturynska their creative relationship. A separate “story” given by visnykers and neoclassic – M. Zerov and E. Malaniuk. In a conversation involving little-known literary estimates and judgments of literary elite of the Ukrainian diaspora.